(3EOGQI GdJejR (B:s (3feGPL hJbfjGJ GdEOGQI aj YUQ GdeYQaI (B/s - (3GdSdej, Ydis ((3GdbGgQI(B: s (3OGQZQjH ddWHGYI hGdfTQ(B, s, 2002)
(3eaGgje hfeGPL EOGQI GdLhOI(B- (3EOGQI GdeYQaI(B- (3bGOI GdJejR(B- (3CfeGW GdJejR(B- (3GdaYGdjI hGdJejR ef efXhQ GSdGejs
Keywords: (3GdEOGQIs; (3GdEOGQI GdeYGUQIs